Organizational Direction Formation of the Scientific School of Management Theory - A. V. Raychenko (Управление)
Systematizing the basic organizational statements, modern science is the base of structure and interaction in any of the studied area. In turn, submitted by the form, disclosed by the content and classified and determined organization becomes a necessary basis for the construction of any science, and each discipline. General organizational beginning of the formation and development of a system of knowledge, and the action, justify and represent a wide variety of scientific schools, based on mutual understanding of their organization. Formation of the organizational direction of the scientific school of management theory defines the scope of the fundamental notions of order, shape, structure, procedures and methods of construction, design and reflection of all existing and submitted to processes and systems.